PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN PEMANUFAKTURAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ratri Dian Hestuningrum; Darsono Darsono (Diponegoro Journal of Accounting, 2012)
The purpose of this research is to find out the influence of firm characteristics on capital structure in pecking order theory perspective of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Characteristics of firms that allegedly affect the capital structure include: firm size , profitability, liquidity, asset structure, price earnings ratio, and growth.The population in this research is a manufacturing company listed on the Stock Exchange period 2005-2010. With purposive sampling method obtained totaling samples 501 companies. Model analysis using multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and capital structure. Using t-test to examine the partial correlation of each independent variable on capital structure.The results showed that the variables of liquidity, profitability, and asset structure have negative and significant influence on capital structure. While the variable firm size and firm growth positively influence the capital structure. The other variable, price earnings ratio do not have influence toward capital structure.